THE CORRELATION BETWEEN THE STUDENTS’ HABIT TO WATCH ENGLISH YOUTUBE CHANNEL AND THEIR SPEAKING SKILL - Khairul Khairul; Rahma Aulia Putri (Universitas Bung Hatta, 2022)
The purpose of this research was to find out the correlation between the second-year students’ habit to watch English YouTube channel and their speaking skill at the English Department of Bung Hatta University. The design of this research was correlational research. The population of this study was the second-year students who registered in the academic year of 2020/2021. Due to the limited number of population members, the researcher used total sampling technique. The number of the sample as respondents in this research was 30 students. The instruments used to get the data were questionnaire and speaking tests. It was found that the reliability index of the questionnaire was 0.82 and the reliability index of the speaking test was 0.72. The result of the data analysis showed that the value of rcalculated of this research was 0.74, while the value of rtable with the level of significance 0.05 and the degree of freedom (df= n-2) was 0.374. It means that the rcalculated was higher than rtable (0.74 > 0.374). Therefore, the alternative hypothesis of this research stating that there is a significant correlation between the second-year students’ habit to watch English YouTube channel and their speaking skillat the English Department of Bung Hatta University was accepted. Based on the result of the data above, it can be interpreted the students’ habit of watching English YouTube channelcan increase their speaking skill University. REFERENCES Albahlal, S. F. (2019). The Impact of YouTube on Improving Secondary School Students’ Speaking Skills: English Language Teachers’ Perspectives. Journal of Applied Linguistics and Language Research, 6(2), 1–17. Almutairi, M. A. (2021). Underachievement in English Speaking Skills among Kuwaiti EFL Students at the College of Basic Education: Possible Causes and Possible Solutions. Journal of Language Teaching and Research, 12(1), 206. Arikunto, S (2012). Dasar-DasarEvaluasiPendidikan. Jakarta: PT. BumiAkasara. Babu H., Rajendra, Buddayya, R., & Gujjarappa, N. L. (2019). Benefits of Videos In YouTube for the Undergraduate Students in Engineering and Technology in India. Webology, 16(2), 57–71. Cambridge University. Cambridge Dictionaries. (2019). Retrieved on April 18, 2019, fromhttps://dictionary.cambridge.org/ Chen, W., Chan, T. W., Wong, L. H., Looi, C. K., Liao, C. C. Y., Cheng, H. N. H., Wong, S. L., Mason, J., So, H. J., Murthy, S., Gu, X., & Pi, Z. (2020). IDC theory: habit and the habit loop. Research and Practice in Technology Enhanced Learning, 15(1). Clear, J. (2018). Atomic Habits: Tiny Changes, Remarkable Results: An Easy & Proven Way To Build Good Habits & Break Bad Ones. New York: Penguin Random House. Dionar, W. S., & Adnan, A. (2019). Improving Speaking Ability of Senior High School. Journal of English Language Teaching, 7(2), 370–374 Duhigg, C. (2012). The Power of Habit: Why We Do What We Do in Life and Business. New York: Random House. Durga, M. (2018). The Need of English Language Skills for Employment Opportunities. Journal for Research Scholars and Professionals of English Language Teaching. Vol 2. Issues 7 Faliyanti, E., & Arlin, M. (2018). the Correlation Between Students’ Habit in Watching English Movie and Vocabulary Mastery At the Sixth Semester At English Education Study Program in the Muhammadiyah University of Metro. Intensive Journal, 1(2), 94. Hussin, R. A. (2020). the Use of Youtube Media Through Group Discussion in Teaching Speaking. English Education Journal, 11(1), 19–33. James, S. E. (2013). Charles Duhigg: The Power of Habit: Why We Do What We Do in Life and Business. Journal of Child and Family Studies, 22(4), 582–584. Khuc, Q. V., Pham, P., & Tran, D. (2021, February 2). Questionnaire design.https://doi.org/10.31219/osf.io/q3um6 Lestari, N. (2019). Improving the Speaking Skill by Vlog (video blog) as Learning Media: The EFL Students Perspective. International Journal of Academic Research in Business and Social Sciences, 9(1), 915–925. Mertler, C. A. (2019). Introduction to Educational Research. Los Angeles: SAGE Publications. Michael, E. A., & Shah, P.M. (2020). Students’ Perception on YouTube Usage in Rural ESL Classroom. International Journal of Academic Research in Business and Social Sciences, 10(3), 410-431. Ningsih, A.F (2019). the Correlation Between Students’ Habit in Watching English Movie and Learning Style Toward Listening Comprehension. Published Thesis. Palangka Raya: State Islamic Institute of Palangka Raya Putri, W. A., (2019).